Phenomenology Study : Family Experience in Elderly Care In Depok Jawa Barat - Yati Sri Hayati; Asti Melani Astari (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2020)
The family has an important role in elderly care at home, where the majority of assistance and long-term care for the elderly is provided by the family. The nurse is responsible for assisting the family in caring for the elderly, so that in the end the family is able to provide elderly care independently at home. This study aims to explore family experiences in caring for the elderly at home. Researchers used qualitative research methods with a phenomenological approach. Data obtained through semi-structured interviews with 6 (six) participants. The research produced 5 themes: care for the elderly is a form of devotion to parents, care for the elderly requires physical and mental readiness, care for the elderly requires knowledge related to the elderly and how to care for the elderly, care for the elderly requires support from extended families, and feel the importance of supporting cadres and health workers. For conclusion, elderly families have a responsibility to meet the needs of the elderly, so that efforts are needed to improve the knowledge and skills of the family in order to properly care for and meet the needs of the elderly.